Development of Augmented Reality E-Booklet to Improve Students' Learning Outcomes on Earth Structure Material - Amalina, Salsabila Laily; Pradana, Mochammad Desta; Anggraini, Atika (AS-SABIQUN, 2025)
This study addresses the persistent issue of low academic performance among Grade VIII students at SMPN 9 Kediri, where the average cognitive score of 68.95 fell below the established minimum mastery criterion (KKTP) of 75. The research aimed to develop an Augmented Reality (AR)-based e-booklet as an instructional medium to enhance student learning outcomes on the topic of Earth's structure. Employing a Research and Development (R&D) methodology guided by the ADDIE model, the study involved 34 students from class VIII A. The learning media integrated text, images, and 3D AR visualizations to support students' understanding of abstract geological concepts. Validation was conducted through expert evaluations in material, design, and media, with feasibility scores of 97.5%, 95.7%, and 97.1%, respectively. Effectiveness was assessed through pretest and posttest analysis using a paired sample t-test and N-Gain calculation. The results indicated a statistically significant improvement (p = 0.000 < 0.05) and an N-Gain score of 0.6597, reflecting a moderate level of effectiveness. The study concludes that the AR-based e-booklet is an effective educational tool for improving learning outcomes. These findings highlight the potential of AR-integrated digital media to facilitate student comprehension of complex scientific content.